Provider and patient burdens of obtaining oral anticancer medications - Geynisman, Daniel M. (Am J Manag Care, 2018)
Oral anti-cancer medications (OAMs) are frequently used to treat patients with cancer. Unlike intravenous chemotherapy, OAMs are covered by prescription drug plans. We examined barriers to initiation of OAMs in 116 prostate and kidney cancer patients (149 unique prescriptions). We found that the median time from initial prescription to prior authorization was 3 days and the median time from initial prescription to patient receipt of drug was 12 days. Seventy three percent of all prescriptions required two or more phone calls and 40% required five or more calls by clinic staff. Out of 107 prescriptions with data available, 54% utilized financial assistance and those required significantly more phone calls (P=0.0001) and led to a longer median time to drug obtainment (P=0.003) compared to those who did not utilize financial assistance. In those with both initial and final copay information available, the initial out-of-pocket mean and median copayments were $1226 and $329.73, but dropped to $124.57 and $25 respectively after utilization of copayment assistance programs, excluding those with a $0 final copay. These early observations suggest that a more efficient process for initiation of OAMs is needed.